La nueva peculiaridad que ejecutan los empleadores, el de hacer firmar letras de cambio o pagares a sus trabajadores que cumplen funciones de confianza, lo cual vulnera sus derechos establecidos en el codigo del trabajo y la constitución - Bustos Freire, Carlos Alberto (2017)
The Constitution of the Republic of Ecuador, in its first articles, mentions the Fundamental Principles, which state that Ecuador is a State of rights, justice, social, democratic, sovereign, independent, unitary, intercultural, plurinational and secular. Among the primary duties of the State, which are shown in Article 3 of the same legal body that manifests in guaranteeing the rights established in the Constitution and international instruments and guarantee the inhabitants the right to Integral Security. To this end, the present Legal Investigation entitled: "THE NEW PECULIARITY EXECUTED BY EMPLOYERS, TO MAKE SIGNED LETTERS OF EXCHANGE OR PAYMENT TO ITS WORKERS WHO COMPLY WITH CONFIDENCE FUNCTIONS, WHICH WOULD VULNERATE THEIR RIGHTS ESTABLISHED IN THE CODE OF WORK AND THE CONSTITUTION", Seeks, through a meticulous Legal-Doctrinal study to solve the existing legal conflict, to guarantee the fulfillment of Labor Rights to workers in Ecuador. My research work has allowed me to analyze and carry out a study on the emergence of the working class, the claim of their rights through the history of humanity and to analyze with legal criteria the Labor Code, and the Constitution of the Republic; And the imperative need to include in the Labor Code provisions that prevent some workers' rights from being violated, using frauds on the part of the employers, such as the signing of executive titles such as bills of exchange or blank pay by the worker As a guarantee to keep your work or to be able to access it. Deeply in this study, there are alarming figures about the level of non-compliance with the constitutional and legal norms related to the trust functions performed by Ecuadorian workers, and it is also clear that there is no policy to demand that these rules be obeyed And effectively meet. Within the content of the present investigation they are developed as follows: Conceptual Framework, where definitions of some terms are described, as well as theories are described on Labor Law. Doctrinal Framework, mentions arguments and opinions of various writers, as well as media publications on the subject. Legal Framework, which analyzes the Constitution of the Republic of Ecuador, the Labor Code and other National standards, concerning the right of workers. Materials and Methods, where I can summarize the methods and techniques used in the development of both documentary and field research, which served as a backup to consolidate the desired results. Presentation of Results, the same ones that were obtained through the application of the Surveys and Interviews, which were carried out this locality, and shaped by means of graphic representations, that allowed to make a quantitative and qualitative analysis of the research topic. Discussion, where the analysis of the problem is presented, carrying out the verification of stated objectives, as well as the contracting of the hypothesis drawn for the problematic of study. Conclusions and Recommendations obtained at the end of the research, to culminate with a sustained and reasoned legal proposal that I consider to be of benefit to our legislation.